The association between the inflammatory response following surgery and post-operative delirium in older oncological patients: a prospective cohort study. (18th February 2022) - Brattinga, Baukje; Plas, Matthijs; Spikman, Jacoba M; Rutgers, Abraham; de Haan, Jacco J; Absalom, Anthony R; van der Wal-Huisman, Hanneke; de Bock, Geertruida H; van Leeuwen, Barbara L
Abstract: Introduction: Post-operative delirium (POD) is associated with increased morbidity and mortality rates in older patients. Neuroinflammation, the activation of the intrinsic immune system of the brain, seems to be one of the mechanisms behind the development of POD. The aim of this study was to explore the association between the perioperative inflammatory response and the development of POD in a cohort of older oncological patients in need for surgery. Methods: In this prospective cohort study, patients 65 years and older in need for oncologic surgery were included. Inflammatory markers C-reactive protein (CRP), interleukin-1 beta (IL-1β), IL-6, IL10 and Neutrophil gelatinase-associated lipocalin (NGAL) were measured in plasma samples pre- and post-operatively. Delirium Observation Screening Scale (DOS) was used as screening instrument for POD in the first week after surgery. In case of positive screening, diagnosis of POD was assessed by a clinician. Results: Between 2010 and 2016, plasma samples of 311 patients with median age of 72 years (range 65–89) were collected. A total of 38 (12%) patients developed POD in the first week after surgery. The perioperative increase in plasma levels of IL-10 and NGAL were associated with POD in multivariate logistic regression analysis (OR 1.33 [1.09–1.63] P  = 0.005 and OR 1.30 [1.03–1.64], P  = 0.026, respectively). The biomarkers CRP, IL-1β and IL-6 were not significantly associated with POD. Conclusions: Increased surgery-evoked inflammatory responses of IL-10 and NGAL are associated with the development of POD in older oncological patients. The outcomes of this study contribute to understanding the aetiology of neuroinflammation and the development of POD.